Cálculo diferencial e integral: uma abordagem no ensino médio - Jálio Araújo da, Silva (2019)
With the systematization of students' admission to universities through ENEM, many schools seek to work the student's time spent in solving questions. And, why not use the calculus? Do educators, in general, have di culties in dealing with calculus, and its various applications? With this, the Di erential and Integral Calculus, is a very important tool for some resolutions of exercises in the scope of Mathematics and Physics. This work consists in the use of Di erential and Integral Calculus to show to the students that it is an optimized tool in some cases and essential for the student's life as a high school or college student. We used the Federal Institute of Maranhão Santa Ines campus, as the center of the research, in which it was made an explanation of the de nition of limits, derived and integral with their respective properties. We believe it is possible to propose improvements on the bene ts of inserting the calculus already in high school. It is hoped that this work will stimulate educators and learners about the challenges of teaching in a more meaningful way, and new approaches in the "everyday"of classes.